Optimization of auditory brainstem response (ABR) test time using level specific (LS) CE-CHIRP® - Dzulkarnain, Ahmad Aidil Arafat; Marzuki, Muhammad Nasrullah; Shahrudin, Fatin Amira; Jamal, Fatin Nabilah; Chahed, Norashikin; Zakaria, Mohd Normani (IIUM Press, 2023)
Introduction: The duration of auditory brainstem response (ABR) test is influenced by the time it takes to acquire the ABR signals. The ABR acquisition time can be reduced by using Level Specific (LS) CE Chirps® stimulus that is known to have better spectral synchrony than the traditional click stimulus. To evaluate the time-efficiency of the LS CE Chirps® stimulus, an objective stopping criteria such as those based on signal to noise ratio (SNR) can be used. Using this technique, the test time for both the ABRs elicited by LS CE Chirps® and click stimuli can be compared based on the fastest stimulus to reach an appropriate SNR. To the authors knowledge, no study has scientifically investigated the use of LS CE Chirps® to reduce the ABR test time. Aim: The present study aimed to compare the number of averages needed to reach the specified SNRs between the ABRs elicited from LS CE Chirp® and click stimuli in normal hearing adults. Methodology: A repeated measures research design was used involving fifteen adult subjects as participants. ABRs were acquired at four intensity levels (80, 60, 40, and 20 dB nHL) and two stimuli (LS CE Chirps® and click stimuli). The ABR signal averaging was stopped when the multiple points F-ratio (Fmp) value reached 3.1. Results: The number of averages between the ABR elicited from LS CE Chirps® and click stimuli were statistically compared. The number of averages to reach Fmp at 3.1 was lower in the ABRs elicited using LS CE Chirps® than the ABRs to click stimuli at all intensity levels. Conclusion: This study demonstrated that ABRs arising from LS-CE-Chirps® stimuli could be acquired faster than ABRs elicited from click stimuli. Implication: The use of LS-CE-Chirps® stimulus has the potential to reduce the ABR acquisition time in comparison to the traditional click stimulus.